2016
DOI: 10.1126/science.aad7154
|View full text |Cite
|
Sign up to set email alerts
|

Artificial electron acceptors decouple archaeal methane oxidation from sulfate reduction

Abstract: Long-term partners uncoupled Methane-munching archaea in marine sediments live closely coupled to sulfate-reducing bacteria in a syntrophic relationship. Surprisingly, however, these archaea do not necessarily need their bacterial partners to survive or grow. Scheller et al. performed stable isotope incubation experiments with deep-sea methane seep sediments (see the Perspective by Rotaru and Thamdrup). Several groups of methane-oxidizing archaea could use a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
301
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(316 citation statements)
references
References 56 publications
14
301
1
Order By: Relevance
“…According to 16S rRNA gene sequences from wetland sediment samples performing AOM, anaerobic methanotrophic archaea (ANME), which are traditionally linked to anaerobic methanotrophy under sulfatereducing (2,26), Fe(III)-reducing (6,8), and artificial electron acceptor-reducing conditions (27), were barely detected in our experiments, with ANME-1b and ANME-3 representing less than 0.5% and 0.2%, respectively, from the archaeal community in all experimental treatments (Fig. 5).…”
Section: Figmentioning
confidence: 94%
“…According to 16S rRNA gene sequences from wetland sediment samples performing AOM, anaerobic methanotrophic archaea (ANME), which are traditionally linked to anaerobic methanotrophy under sulfatereducing (2,26), Fe(III)-reducing (6,8), and artificial electron acceptor-reducing conditions (27), were barely detected in our experiments, with ANME-1b and ANME-3 representing less than 0.5% and 0.2%, respectively, from the archaeal community in all experimental treatments (Fig. 5).…”
Section: Figmentioning
confidence: 94%
“…Only two studies investigated methane oxidation coupled to Fe 3+ or Mn 4+ reduction in naturally enriched samples of ANME-2 archaea. Using marine samples, Nauhaus et al reported that methane oxidation was not coupled to the reduction of ferrihydrite, iron citrate, humic acids, and anthraquinone-2,6-disulfonate (AQDS) (21), whereas recently Scheller et al showed that marine samples containing ANME-2a, ANME-2c, and other archaea oxidized methane in the presence of chelated iron and could couple methane oxidation activity to AQDS reduction (22). Nevertheless, in nature, metals predominantly occur in particulate forms, which are more difficult to access (15,16,19,23).…”
Section: Significancementioning
confidence: 99%
“…Recently, using a sample that contained ANME-2a and ANME-2c, Scheller et al reported 13 CO 2 production from 13 CH 4 oxidation in the presence of ferric citrate (22). Due to the notorious difficulties associated with measuring dissolved ferrous (Fe 2+ ) iron in complex media or natural samples, the stoichiometric relationship between the reduction of Fe 3+ and oxidation of CH 4 was not shown (22). Here, in a setup with destructive sampling, where total CO 2 and Fe 2+ could both be measured, we observed a near-perfect fit to the theoretically expected stoichiometry of 1:8 ( Fig.…”
Section: Significancementioning
confidence: 99%
“…In marine seeps, AOM is predominantly catalyzed by a symbiosis of anaerobic methane-oxidizing euryarchaeotes (ANME) with sulfate-reducing bacteria (SRB), which form consortia of varying cell numbers (∼10 to ∼10 5 cells) and morphology (7,26). Their syntrophic partnership is hypothesized to be mediated by direct electron transfer (27)(28)(29) and/or diffusible intermediates (30,31).…”
Section: Significancementioning
confidence: 99%